An Islamic Perspective in Managing Religious Diversity - Wani, Hilal Ahmad (Religions, 2015)
This paper examines the concept of diversity as mentioned in the Qur'an and how commonalities in diverse religions may be used as a model for civilizational dialogue towards achieving harmony. This study reveals that religious and cultural diversity are laws of nature which cannot be changed while the concept of identity is a contested issue in modern discourse. Results also show that peace may be established among diverse religions through their commonalities and the best way to exploit these commonalities and to reduce the religious divide is through civilizational dialogue. The Alternative Dispute Resolution (ADR) and other methods for changing the nature of religious differences and reaching a consensusthus arriving at a peaceful co-existenceare also discussed. It was found that people are often misguided or divided in the name of religion and culture, despite the fact that the philosophy of every religion is based on peace and harmony.